Investigating the factors of workforce agility at Lembaga Zakat Negeri Kedah / Abdul Rahman Abdol Razak - Abdol Razak, Abdul Rahman (2019)
Recognizing that a very low number of studies have been done on the agility of the workforce, current research aims to assess the impact of organizational practices in the form of organizations learning and training, compensation, involvement, teamwork, information systems and also psychological empowerment on the workforce agility. The research has been conducted in Lembaga Zakat Negeri Kedah (LZNK). Qualitative data have been collected consist of 100 employees at Lembaga Zakat Negeri Kedah (LZNK). Data have been analyzed using descriptive analysis, reliability analysis, variable analysis, correlation analysis and multiple regression analysis. Hence, this study discovered that organizational practices related to workforce agility proved that organizational practices can improve the traits and behavior of the workforce.